2002
DOI: 10.1088/0026-1394/39/6/8
|View full text |Cite
|
Sign up to set email alerts
|

International comparisons of He-Ne lasers stabilized with127I2at     633 nm (July 2000). Part X: Comparison of INMETRO (Brazil), INTI (Argentina), NRC-INMS (Canada), CENAM (Mexico), and BIPM lasers at     633 nm

Abstract: This paper reports the tenth set of results of a series of grouped laser comparisons from national laboratories undertaken by the Bureau International des Poids et Mesures (BIPM) at the request of the Consultative Committee for Length (CCL), formerly the Consultative Committee for the Definition of the Metre (CCDM), for the periods July 1993 to September 1995 and March 1997 to March 2001. As with the previous nine comparisons, this one is expected to be listed as a key comparison in the context of the ongoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the past, ensembles of 633 nm laser standards were compared in order to verify the stability of the ensemble-averaged frequencies. Results from comparison data showed that kilohertz level reproducibilities could be observed for the travelling laser systems when values are compared over a period of time [20][21][22]. In general, the relative frequency offsets of the standards constructed in different laboratories were found to satisfy the 10 kHz standard uncertainty set by the CIPM in the 2001 guidelines for the practical realization of the metre [3].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the past, ensembles of 633 nm laser standards were compared in order to verify the stability of the ensemble-averaged frequencies. Results from comparison data showed that kilohertz level reproducibilities could be observed for the travelling laser systems when values are compared over a period of time [20][21][22]. In general, the relative frequency offsets of the standards constructed in different laboratories were found to satisfy the 10 kHz standard uncertainty set by the CIPM in the 2001 guidelines for the practical realization of the metre [3].…”
Section: Introductionmentioning
confidence: 89%
“…This conclusion was originally based upon international laser comparisons of INMS 2 during the period 1993 to 2000. In these measurements, the operating frequency was corrected to the mise-en-pratique operating conditions and referenced to the value of the stationary BIPM 4 laser [20][21][22]. Figure 2 that most of the observed change is due to the INMS 2 laser and that the BIPM 4 laser did not drift appreciably in frequency during the period 1993 to 2000.…”
Section: Shift Coefficient Inms 2 Inmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The very first formal comparison termed BIPM.L‐K10 was performed from 1989 till 2000 . The frequency standards compared were iodine‐stabilized He–Ne lasers (see Section 4.3 below) operated by 46 NMIs all over the world.…”
Section: Optical Frequency Standardsmentioning
confidence: 99%